THE ORIGINS OF THE ATHENIAN ECONOMIC ARCHE - Kallet, L (2013)
Histories of the Athenian Empire (478-404 BC) have traditionally been offered as political and military narratives. They explain the origins of a naval alliance created in 478/7 BC, the so-called Delian League under Athenian leadership and its development into an 'empire' (arche) sometime in mid-century. Moreover, most treat the phenomenon as comprehensible as a self-contained period of enquiry. This article takes issue with both approaches. Through close examination of a wide variety of evidence connected with Athenian activity during the formative years of the 'Delian League' (478 to ca. 465), it argues that the Athenians made immediate use of the League navy and funds to appropriate resources, profits and territory for themselves, especially in Thrace, beginning with the capture of Eion on the Strymon, but also that these interests explain other early activities. Finally, it argues that the Athenians' economic behaviour should be understood in the context of Athenian aims and activities in the Archaic period. © 2013 The Society for the Promotion of Hellenic Studies.